Conceptual Evolution of Development from Perspective of Radicalism - hadi ajili; mahdi rezaee (سپهر سیاست, 2019)
The aim of this research is to study Radical theory ideals in Global political economy with emphasis on development. Thus, the main research question is the nature and meaning of development in the various Radicalism approaches including (such as) studies Colonialism and Imperialism, Dependency theory, Neocolonialism, Globalization, and the evolution of development concept in each theories. As his research is done in descriptive-analytic method and by desk research, the findings show that all theories has been presented (raised) permanent connection (relation) and links between dynamics of Capitalism system and its functions and the concept of development and underdevelopment in different national and international levels, and the inherent characteristics of capitalist system including exploitation, inequality, and inhuman relations has described in all theories. While understanding Radical’ ideals of  Radicalism theory in global political economy or international relationships has many complicated philosophy, but it contradict ideal western human as development basis, and the emphasis is on relative and indigenous nature of different communities ideals in relation to the issue of development. The concept of development, as how to make society equal in the light of economic relationships and production is not in the focus (heart) of attention, but the important matter is the emphasis on humanizing the existing relationships at all levels. However, Radicals have key role in development and promotion of literacy and philosophy related to development and underdevelopment issues, but in fact, they cannot provide an example of development model based on their opinions and assumptions on the national and international level.